Solcoseryl as a Powerful Radioprotective Compound - Bauer, D.; Locker, A. (Nuklearmedizin - NuclearMedicine, 1974)
In adult inbred mice the blood extract Solcoseryl®, when applied singly intraperitoneally or perorally is able to protect over a comparatively large dose range against y-irradiation of a lethal dose whereby up to 100% survivors are obtained (as compared with practically no survival in the untreated, only irradiated animals of the control series). The effect of a low dose of Solcoseryl eliciting only approx. 50% survivors among the animals can be improved up to 100% if the animals were subject to heat adaptation for a period of 6 weeks prior to the Solcoseryl treatment and irradiation and heat adaptation continued during the subsequent observation time.